The Effects of Oil Price Shocks and Economic Fluctuations of Trading Partners on Iran's Ports Throughput - Mirzaei, Mehdi; Parsa, Hojat (Transactions on Maritime Science, 2019)
This study aims to estimate the effects of oil price shocks on seaborne trade in Iran; in particular, port throughput of three leading ports through economic fluctuations of three major trading partners of Iran, based on quarterly data for the period of 1999Q2 to 2018Q1. We apply a standard vector autoregressive (VAR) approach using Cholesky decomposition. The results indicate that with increasing oil revenues in short-run, seaborne trade be further directed towards Shahid Rajaei port while rising oil revenues changes the combination of goods handled in Emam Khomeini and Bushehr ports. In the long run, the share of oil price fluctuations in explaining the variations of Shahid Rajaei port throughput is higher than the other two. In fact, increases in oil revenues cause an increase in the volume of industrial and containerized seaborne cargo trade.